2021
DOI: 10.1007/s00784-021-03801-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flowable liners on the shrinkage vectors of bulk-fill composites

Abstract: Objectives This investigation evaluated the effect of flowable liners beneath a composite restoration applied via different methods on the pattern of shrinkage vectors. Methods Forty molars were divided into five groups (n = 8), and cylindrical cavities were prepared and bonded with a self-etch adhesive (AdheSe). Tetric EvoCeram Bulk Fill (TBF) was used as the filling material in all cavities. The flowable liners Tetric EvoFlow Bulk Fill (TEF) and SDR were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(131 reference statements)
1
12
0
2
Order By: Relevance
“…Shrinkage and voids during restoration in both conventional and bulk-fill composites are the major issues. In a recent study, it was found that by applying a thin or thick layer of flowable liner in an incremental way underneath Tertic EvoCeram bulk-fill restoration could act as a stress reliever [ 36 ]. In another study, Micro-CT was employed to evaluate the internal void in different bulk-fill composite restorations with different types of insertion techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Shrinkage and voids during restoration in both conventional and bulk-fill composites are the major issues. In a recent study, it was found that by applying a thin or thick layer of flowable liner in an incremental way underneath Tertic EvoCeram bulk-fill restoration could act as a stress reliever [ 36 ]. In another study, Micro-CT was employed to evaluate the internal void in different bulk-fill composite restorations with different types of insertion techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The use of flowable composite resins has increased dramatically since their introduction in 1995; their main indication was as a base or liner under posterior composite resin restorations. Their fluidity ensures a perfect adaptation to the walls of the cavity, which reduces the risk of air trapping and the formation of voids; this helps to reduce stress at the margin of the restoration [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Their composition consists of a reduction in the number of fillers from 20% to 25% and an increase in the monomeric diluents, which results in a decrease in viscosity and an improvement in fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…using microcomputed tomography concluded that application of a flowable liner of thickness from 0.5 to 2 mm led to favorable shrinkage patterns and better adaptation to cavity walls, thus acting as stress reliever. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%